A two-week gaming abstinence reduces Internet Gaming Disorder and improves mental health: An experimental longitudinal intervention study. (September 2022) - Brailovskaia, Julia; Meier-Faust, Julius; Schillack, Holger; Margraf, Jürgen
Abstract: Since the COVID-19 outbreak, digital gaming has become a welcome pastime and distraction for many people. However, this phenomenon can have severe consequences; intensive digital gaming can foster the Internet Gaming Disorder (IGD) and negatively affect mental health. The present experimental longitudinal study investigated the consequences of a conscious abstinence from gaming in a German sample. The experimental group ( N = 131; age: M = 26.21, SD = 7.70) did not engage in gaming for two weeks; the control group ( N = 140; age: M = 25.10, SD = 4.94) maintained its gaming time and habits. Gaming-related variables and mental health-related variables were assessed via online surveys at five measurement time points (baseline, intermediate status, post-intervention, one-month follow-up, three-month follow-up). The intervention significantly reduced gaming time, gaming flow, IGD, daily stress, and anxiety symptoms. Moreover, we found a significant improvement in positive mental health. The effects were stable over the three months of the investigation. Thus, we could show that a conscious and controlled, short-term abstinence from gaming leads to reduced IGD and a better mental health. The present results emphasize that conscious periods of gaming abstinence could be an effective step in the clinical context and in mental health prevention programs, especially during a pandemic such as the COVID-19 outbreak. Highlights: Two-week gaming-abstinence reduces gaming time and gaming flow longitudinally. Two-week gaming-abstinence reduces the level of Internet Gaming Disorder (IGD). Two-week gaming-abstinence reduces the experience of daily stress and anxiety symptoms. Two-week gaming-abstinence increases positive mental health. Temporary gaming-abstinence can protect mental health during the COVID-19 outbreak.